Developing Business Strategy for Hijab Alsa - Adwitya Setiawan, Amanda; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2017)
Abstract. Hijab Alsa is a company that producing and selling women’s Muslim clothing in Indonesia. Hijab Alsa was founded in December 2014 by Ali Hanif who is a man and become a CEO of Hijab Alsa until today. Hijab Alsa has been have inconsistent sales in month by month after Ali Hanif was starting run the Hijab Alsa business. It comes early problem that will be affecting whole business and become starting point to find the core problem of Hijab Alsa’s business strategy. This research is aimed find the best strategy for Hijab Alsa based on Blue Ocean Strategy and Diamond Strategy. This research is using combination of qualitative and quantitative methods that developed by using questionnaire, depth interview, focus groupd discussion, and data support. The result shows Hijab Alsa need to improve the strategy from cost-leadership strategy into differentiation strategy. The improvement is based on eliminating factors of variation and design of product; reducing factors of price and service to customer; raising factors of quality, social media (instagram), product availability, and simplicity to making order; and creating factors of influencer, information, and organized virtual retailing. The final result of the research shows Hijab Alsa has new value to run the businesss. The new value of Hijab Alsa is providing website as become multi-side platform to delivering system and product for self-service of accessible within available product and affordable price. So, Hijab Alsa can developed their business and achieve their sustainability advantages in the future.Keywords: Women Muslim product,Business Strategy, Blue Ocean Strategy dan Diamond Strategy.